2013
DOI: 10.1111/j.1540-4781.2012.01421.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Syntactic Complexity: Developmental Profiling of Individuals Based on an Annotated Learner Corpus

Abstract: This study tracks the development of syntactic complexity in the writing of two beginning German as a second language learners with English as a first language over four semesters of collegiate language study by using developmental profiling techniques applied to an annotated learner corpus. The focus of the investigation is on individual developmental pathways and differences between learners who follow the same instructional sequences. The study explores variation in terms of frequencies of the selected comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 52 publications
5
41
0
6
Order By: Relevance
“…Several longitudinal studies have also been carried out to track and compare learner development in syntactic complexity over time (e.g., Casanave, 1994;Ishikawa, 1995;Mazgutova & Kormos, this volume;Norrby & Håkansson, 2007;Ortega, 2000Ortega, , 2003Stockwell & Harrington, 2003;Vyatkina, 2013;Vyatkina, Hirschmann, & Golcher, this volume). For example, Norrby and Håkansson (2007) tracked adult learners of Swedish over a one-year period and reported that they can be classified into four types: The Careful, The Thorough, The Risk-taker, and The Recycler, based on the relationship between morphosyntactic development and complexity exhibited in their language production.…”
Section: Syntactic Complexity and Second Language Writingmentioning
confidence: 98%
See 2 more Smart Citations
“…Several longitudinal studies have also been carried out to track and compare learner development in syntactic complexity over time (e.g., Casanave, 1994;Ishikawa, 1995;Mazgutova & Kormos, this volume;Norrby & Håkansson, 2007;Ortega, 2000Ortega, , 2003Stockwell & Harrington, 2003;Vyatkina, 2013;Vyatkina, Hirschmann, & Golcher, this volume). For example, Norrby and Håkansson (2007) tracked adult learners of Swedish over a one-year period and reported that they can be classified into four types: The Careful, The Thorough, The Risk-taker, and The Recycler, based on the relationship between morphosyntactic development and complexity exhibited in their language production.…”
Section: Syntactic Complexity and Second Language Writingmentioning
confidence: 98%
“…Specifically, complexity developed hand in hand with grammatical proficiency for The Careful and Thorough, ahead of grammatical proficiency for The Risk-taker, and was avoided despite evidence of grammatical proficiency by The Recycler. Vyatkina (2013) tracked the development of syntactic complexity in the writing of two beginning learners of German over four semesters. She reported that while there was a general developmental trend towards increasing the frequency and range of syntactic complexity features, the two learners diverged from one another in the latter half of the observation period.…”
Section: Syntactic Complexity and Second Language Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is only recently that writing research and studies in the field of English for Academic Purposes (EAP) have started to focus on the linguistic features of students' writing and how they improve along with developments in proficiency in various instructional contexts (see, for example, the collection of studies introduced in a recent special issue of the Journal of Second Language Writing, guest edited by Connor-Linton & Polio, 2014). The development of the syntactic complexity of students' writing has been at the centre of a number of studies in recent years (e.g., Byrnes, 2009;Byrnes & Sinicrope, 2008;Crossley & McNamara, 2014;Shaw & Liu, 1998;Vyatkina, 2013), but only a few studies have considered lexical development in conjunction with syntactic changes in students' written production (for exceptions see Bulté & Housen, 2014;Storch & Tapper, 2009;Verspoor, Lowie, & van Dijk, 2008;Vyatkina, 2012). In our study, we investigated how the lexical and syntactic characteristics of L2 learners' writing changed during the course of an intensive EAP programme which aims to prepare international students for university studies at undergraduate and postgraduate levels in the UK.…”
Section: Introductionmentioning
confidence: 98%
“…Some recent longitudinal studies of L2 writing have examined the development of syntactic complexity, but these were mostly conducted with university learners of German at beginning (Vyatkina, 2012(Vyatkina, , 2013 and advanced levels (Byrnes, 2009;Byrnes & Sinicrope, 2008). The studies of Byrnes (2009) and Byrnes and Sinicrope (2008) reveal that -parallel with developments in proficiency -increase in nominalisation, the use of relative clauses, and grammatical metaphor can be observed.…”
Section: Introductionmentioning
confidence: 99%